2013
DOI: 10.1111/jphp.12060
|View full text |Cite
|
Sign up to set email alerts
|

(S)-[6]-Gingerol inhibits TGF-β-stimulated biglycan synthesis but not glycosaminoglycan hyperelongation in human vascular smooth muscle cells

Abstract: The activity of (S)-[6]-gingerol to inhibit TGF-β-stimulated biglycan synthesis suggests a potential role for ginger in the prevention of atherosclerosis or other lipid-binding diseases. The signalling studies indicate a novel site of action of (S)-[6]-gingerol in inhibiting TGF-β responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Thrombin signalling pathways leads to proteoglycan synthesis, GAG elongation [10] and an increase in the mRNA expression of GAG synthesizing genes [11]. TGF-β mediated proteoglycan synthesis [20,32] and GAG gene expression [19,21] are regulated by the phosphorylation of transcription factor Smad2 in the linker region. Multiple signalling pathways are involved in Smad2 linker region phosphorylation [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin signalling pathways leads to proteoglycan synthesis, GAG elongation [10] and an increase in the mRNA expression of GAG synthesizing genes [11]. TGF-β mediated proteoglycan synthesis [20,32] and GAG gene expression [19,21] are regulated by the phosphorylation of transcription factor Smad2 in the linker region. Multiple signalling pathways are involved in Smad2 linker region phosphorylation [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…The shift toward the uPA-enriched profibrinolytic state favors renal collagen degradation. Given its pathophysiological role, studies into TGF-β1 have found that [6]-gingerol inhibits its stimulation of myofibroblast differentiation and collagen production in nasal polyp-derived fibroblasts [53] and of proteoglycan core protein synthesis in human vascular smooth muscle cells [54]. In the present study, fructose-induced upregulation of MCP-1, CCR-2, IL-6, TGF-β1 and PAI-1 gene expression in kidney was suppressed by ginger supplement (50 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…The S-enantiomer of 6-GN was found to exhibit a potent anti-atherosclerotic activity, by inhibiting the incorporation of [35S]-Met/Cys into proteoglycans and total proteins in human vascular smooth muscle cells. It also inhibited TGF-b-stimulated proteoglycan core protein synthesis and biglycan mRNA expression (Kamato et al, 2013).…”
Section: Cardiovascular Activitymentioning
confidence: 99%